Faktor Yang Mempengaruhi Audit Delay - Dwi Puryati (JAK (Jurnal Akuntansi) Kajian Ilmiah Akuntansi, 2020)
Company is going public in Indonesia are required to publish their financial reporting that have been audited by an external auditor in accordance with the specified time. However in practice there are still companies that are late in submitting financial reporting. This research aims to examine the effect of tenur audite, audit opinion and size company to audit delay in manufacturing companies listed in Indonesia Stock Exchange on 2015-2017. The population in this reserch is manufacturing companies listed on the Indonesia Stock Exchange in 2015-2017 with total number of 152 companies. The sample selected by random sampling with the number of samples calculated by the Solvin Formula, and obtained the result of 60 of minimum samples. The data analysis technique used F and t examined. . The results of the study show that simultaneously tenur audite, audit opinion and company size have a significant effect on audit delay. While partially tenur audite and audit opinion have a significant effect on audit delay, and company size does not significantly effect on audit delay.